Adaptation and validation of the modified weight bias internalization scale (WBIS-M) in Brazilian adults - Paula Victoria Sozza; Eva Penelo; Maria Fernanda Laus; David Sánchez-Carracedo; Sebastião Sousa Almeida; Telma Maria Braga Costa (PLoS ONE, 2025)
Internalized weight stigma refers to individuals’ self-stigmatization, leading to self-devaluation. This research aimed to conduct an adaptation and validation study of the Modified Weight Bias Internalization Scale (WBIS-M) for Brazil. A sample of 418 adults (253 women; mean age = 30.8 years, SD = 10.4) completed the WBIS-M and measures of anti-fat attitudes, body image, disordered eating, binge eating, and self-esteem. Exploratory factor analyses (EFA) and confirmatory factor analyses (CFA) were conducted to examine the factor structure of the WBIS-M. Measurement invariance across gender was tested with multigroup CFA. Internal consistency was assessed using omega and alpha. Relationships between the WBIS-M scores and external measures were analyzed using Pearson’s and Spearman’s correlations, t-tests, and Cohen’s d for effect size. EFA and CFA showed that the 10-item and 1-factor WBIS-M model fit reasonably well (CFI and TLI ≥ .98, SRMR ≤ .06, although RMSEA ≤ .12). Full metric and full scalar invariance evidenced equivalence across genders. The internal consistency reliability coefficients were satisfactory (α and ω = .94). A higher WBIS-M score was linked to greater body dissatisfaction, restrictive/compensatory behaviors, food/weight concerns, binge eating severity, and lower self-esteem. Women and those with a higher BMI had higher WBIS-M scores. Finally, the Brazilian WBIS-M’s 10-item score is a valid and reliable measure for assessing weight self-stigma in adults.